2010
DOI: 10.1176/appi.neuropsych.22.4.417
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Performance on the MMSE and the DRS-2 Among American Indian Elders

Abstract: Little is known about factors that predict older American Indians’ performance on cognitive tests. This study examined 137 American Indian elders’ performance on the MMSE and the Dementia Rating Scale—Second Edition (DRS-2). Multivariate regression identified younger age, more education, not receiving Supplemental Security Income, and frequent receipt of needed health care as predictors of better performance on the MMSE. Better performance on the DRS-2 was predicted by more education, boarding school attendanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In previous studies to psychometrically evaluate the Mini-Mental State Examination and the Consortium to Establish a Registry for AD tests, 20,40 albeit with smaller numbers of participants, American Indian participant scores were compared with age-adjusted and education-adjusted normative data from NHW, 41 with 11% of American Indians scoring below threshold. In addition, previous research has shown that education length, quality, and degree of achievement are associated with variance and validity on MoCA (and 3MSE) testing, with high score variance in low educational settings.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies to psychometrically evaluate the Mini-Mental State Examination and the Consortium to Establish a Registry for AD tests, 20,40 albeit with smaller numbers of participants, American Indian participant scores were compared with age-adjusted and education-adjusted normative data from NHW, 41 with 11% of American Indians scoring below threshold. In addition, previous research has shown that education length, quality, and degree of achievement are associated with variance and validity on MoCA (and 3MSE) testing, with high score variance in low educational settings.…”
Section: Discussionmentioning
confidence: 99%
“…We used raw MMSE scores in our analysis, because we wished to directly compare findings in a premanifest and manifest cohort (Table 3), and previous studies have also found problems in the interpretation of transformed MMSE scores in specific populations (44). When we conducted an analysis after transforming MMSE scores to Z scores using established normative data (published 26 years ago) (45) to ascertain the potential influence of this approach to MMSE score interpretation on the study results, we observed two differences in the results of the multivariate regression following this analysis.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Among the elderly, the American Indian and Alaska Native population is increasing twice as fast as the American population as a whole (Norris et al, 2012). In addition to more American Indians living to an advanced age, this population has higher rates of conditions (e.g., diabetes, heart disease) that can adversely affect cognitive functioning (Center for Disease Control, 2003;Denny, Holtzman, & Cobb, 2003;Evans & Kantrowitz, 2002;Harris, Albaugh, Goldman, & Enoch, 2003;Jervis et al, 2010;Langlois et al, 2003;Patterson Silver Wolf [Adelv unegv Waya], Duran, Dulmus, & Manning, 2014;Spicer et al, 2003;Steele, Cardinez, Richardson, Tom-Orme, & Shaw, 2008). Whereas the literature suggests that Alzheimer disease (AD) may be less common in some American Indian tribes than in Caucasians (Henderson et al, 2002;Hendrie et al, 1993) and may have a later age of onset (Rosenberg et al, 1996), relatively little is known about cognitive assessment in this population (Jervis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%